Screening and characterization of thermostable lipases-producing bacteria from Sabah Hot Springs - Nurshafrina Aida, Yahya; Bak Zaibah, Fazal; Rafida, Razali; Clemente Michael Wong, Vui Ling; Zarina, Amin; Chor Leow, Thean; Cahyo, Budiman (Malaysian Society for Microbiology, 2025)
Aims: This study was aimed to screen lipase-producing bacteria (LPB) from Tawau and Poring hot springs in Sabah, Malaysia, identify the best bacterium and characterize its lipolytic activity. Methodology and results: The sediment and water samples from the hot springs were used to screen for LPB using Luria-Bertani (LB) agar containing tributyrin as a screening medium at 50 °C. The screening process yielded eight LPB isolates (C1-C8) from the Poring hot spring sediment sample. The specific lipolytic activity of the crude enzymes obtained from these isolates against the p-nitrophenol palmitate substrate ranged from 0.01×10-2 U/mL (C7) to 6.90×10-2 U/mL (C5). The optimum temperature for their activity ranged from 40 °C (C6) to 75 °C (C5), indicating that they were moderate thermophilic enzymes. These LPB isolates exhibited an optimum pH range of 6.0 to 8.0 and were relatively stable in the presence of metal ions, detergents, or dimethyl sulfoxide. The LPB isolate with the highest optimum temperature activity (C5) was identified based on BLAST results of 16S rRNA gene sequence as a species of Serratia with an optimum growth temperature of 65 °C. Conclusion, significance and impact of study: The study confirmed that Sabah hot springs are potential sources of thermostable LPB with unique properties that may be useful in lipid-processing-related industries.